PENGARUH BABY MASSAGE TERHADAP PERTUMBUHAN DAN PERKEMBANGAN BAYI USIA 3-6 BULAN DI WILAYAH KERJA PUSKESMAS II SUKAWATI TAHUN 2021 - Ayuk Widiani Ni Nyoman; Anggun Pratiwi Ni Putu; Diah Mariani Ni Kadek (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: Growth and development are essential to acknowledge in infancy. Stimulation plays a meaningful role in improving the baby development. This study aimed to determine the effect of baby massage on the growth and development of infants aged 3-6 months. Method: This study was using a Quasi-Experimental design with a Pretest-Posttest Control Group Design approach and was implemented in the work area of Puskesmas II Sukawati. The sample of this study subsist of 30 infants (15 infants as the control group and 15 infants as the treatment gr oup). Result: This study showed that after 4 weeks of treatment, there was no significant effect of baby massage on weight gain with p value = 0.187 (> 0.05), along with body length revealed none significant change with p value = 0.480 (> 0.05), but had significant effect on infant development with p value = 0.009 (< 0.05). Conclusion: There was no significant effect of performing baby massage to the growth of infants aged 3 -6 months both from the variables of weight and body length. There is a significant effect of performing baby massage on the development.